2006
DOI: 10.1096/fj.06-5910fje
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative molecular and cellular networks regulate Toll‐like receptor‐dependent inflammatory responses

Abstract: Viral and bacterial pathogens cause inflammation via Toll-like receptor (TLR) signaling. We have shown that effective responses to LPS may depend on cooperative interactions between TLR-expressing leukocytes and TLR-negative tissue cells. The aim of this work was to determine the roles of such networks in response to agonists of TLRs associated with antiviral and autoimmune responses. The TLR3 agonist poly(I:C) activated epithelial cells, primary endothelial cells, and two types of primary human smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(128 citation statements)
references
References 55 publications
12
116
0
Order By: Relevance
“…Poly(I:C) also induced significant IL-8 release from HUVECs ( Fig. 2A, right panel), consistent with previous studies [15]. Dose titration of poly(I:C) with concentrations ranging from 1-100 μg/ml showed that approximately 25 μg/ml poly(I:C) resulted in maximal IL-8 release from SLK cells (data not shown), and this concentration was used in all subsequent experiments.…”
Section: Human Kaposi's Sarcoma Slk Cells Produce Il-8 In Response Tosupporting
confidence: 90%
“…Poly(I:C) also induced significant IL-8 release from HUVECs ( Fig. 2A, right panel), consistent with previous studies [15]. Dose titration of poly(I:C) with concentrations ranging from 1-100 μg/ml showed that approximately 25 μg/ml poly(I:C) resulted in maximal IL-8 release from SLK cells (data not shown), and this concentration was used in all subsequent experiments.…”
Section: Human Kaposi's Sarcoma Slk Cells Produce Il-8 In Response Tosupporting
confidence: 90%
“…Strikingly, TNF-␣ regulates the expression of TLRs, including TLR9, TLR5, and TLR22, in these cells but has negligible effects on macrophages. Similarly, mammalian endothelial cells are endowed with several TLRs, which allows them to cooperate with professional phagocytes in the recognition of microbes and the induction of inflammation (42,43). Interestingly, TNF-␣ and TLR ligands also substantially increased the expression of MHC class II and CD83 in endothelial cells, which might suggest a role for fish endothelial cells and TNF-␣ in Ag presentation.…”
Section: Discussionmentioning
confidence: 99%
“…CXC chemokine receptor (CXCR)3 is the most abundantly expressed chemokine receptor on human lung mast cells within the ASM bundle. Human lung mast cell migration is induced by the CXCR3 ligand CXCL10, which is released preferentially from Th1-stimulated asthmatic ASM cells compared with those from healthy controls [140] and is released in response to Toll-like receptor-3 activation [141]. Interestingly, Th2-stimulated ASM from asthmatics is chemotactic for mast cells compared with nonasthmatic ASM mediated via activation of CCR3 and CXCR1.…”
Section: What Mechanisms Are Involved In Selective Localisation?mentioning
confidence: 99%